Effects of Maternal Tissue Mortality on the Early Development of Acropora tenuis - Nurfaida Salam Manibpel Dumato; Christine C. Baran; Maria Vanessa Baria-Rodriguez (Marine Science Department Diponegoro University, 2026)
As coral reefs face persistent compounded pressure from anthropogenic and environmental stressors, there is a need to assess the capacity of existing colonies on the reef to produce viable offspring. This study evaluated the impacts of maternal health, characterized by tissue mortality, on the reproductive outcomes and early development of Acropora tenuis, a vital reef-building species in the Indo-Pacific region. Specifically, this study focused on the fertilization success, larval development, larval survival, and settlement behavior of individually crossed A. tenuis colonies. In April 2024, ten colonies were collected from Caniogan Reef in the Bolinao-Anda Reef Complex, northwestern Philippines. Six colonies were categorized as healthy (0% tissue mortality) while four exhibited varying degrees of tissue mortality (10-40%). On April 27, four healthy and two unhealthy colonies spawned, resulting in three healthy and two unhealthy crosses, respectively. Results showed that Healthy crosses had higher fertilization success and normal larvae than Unhealthy crosses (Two-way ANOVA, P < 0.05), highlighting the influence of maternal fitness on offspring viability. Larval survival of both maternal health conditions did not vary over 10 days. Lastly, although CCA treatments initially improved settlement rates for larvae from both maternal health conditions, further analysis showed no significant differences over time, indicating that maternal health did not directly affect larval settlement during the experiment. These results underscore the vital importance of maternal health in producing viable gametes under compounded environmental and anthropogenic stresses, emphasizing the need to prioritize coral health in sexual propagation for coral culture and restoration.